Beyond Job Lock: Impacts of Public Health Insurance on Occupational and Industrial Mobility - Ammar Farooq; Adriana Kugler (Institute for the Study of Labor (IZA), 2016)
We examine whether greater Medicaid generosity encourages mobility towards riskier but better jobs in higher paid occupations and industries. We use Current Population Survey Data and exploit variation in Medicaid thresholds across states and over time through the 1990s and 2000s. We find that moving from a state in the 10th to the 90th percentile in terms of Medicaid income thresholds increases occupational and industrial mobility by 7.6% and 7.8%. We also find that higher income Medicaid thresholds increase mobility towards occupations and industries with greater wage spreads and higher separation probabilities, but with higher wages and higher educational requirements.
Keywords: I13; J6; 330; Medicaid; job lock; public health insurance occupational mobility; industrial mobility; occupational mismatch